2018
DOI: 10.1155/2018/1873582
|View full text |Cite
|
Sign up to set email alerts
|

Relapsing Polychondritis with Meningoencephalitis Refractory to Immunosuppressant Therapy

Abstract: Meningoencephalitis is a rare complication of relapsing polychondritis. We report a case of a 25-year-old male who presented with visual hallucinations and symptoms of depression and anxiety, white matter changes on MRI, and CSF lymphocytosis, along with inflammatory chondritis seen in his auricle cartilage biopsy. Eventually he was given the diagnosis of RP presenting with meningoencephalitis based on CSF analysis, brain MRI findings, negative serologies, and neurologic exam findings. The patient's clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
(9 reference statements)
0
5
1
Order By: Relevance
“…Similar to the 2020 publication, Fujiki et al 7 reported 2 cases of nonherpetic nonparaneoplastic limbic encephalitis associated with RP in 2004 that were successfully evaluated and monitored with MRI, focusing specifically on the medial temporal lobe regions. In contrast to the report by Al-Tabbaa and Habal, 5 both patients were successfully treated with high-dose intravenous corticosteroids and later weaned off. However, later, MRI results showed atrophy and damage to the medial temporal lobe and dilation of the temporal horns of the lateral ventricle, indicative of irreversible ischemic injury.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…Similar to the 2020 publication, Fujiki et al 7 reported 2 cases of nonherpetic nonparaneoplastic limbic encephalitis associated with RP in 2004 that were successfully evaluated and monitored with MRI, focusing specifically on the medial temporal lobe regions. In contrast to the report by Al-Tabbaa and Habal, 5 both patients were successfully treated with high-dose intravenous corticosteroids and later weaned off. However, later, MRI results showed atrophy and damage to the medial temporal lobe and dilation of the temporal horns of the lateral ventricle, indicative of irreversible ischemic injury.…”
Section: Discussioncontrasting
confidence: 70%
“…The unique and variable presentation of RP in the CNS is best appreciated when contrasting the case reports, diagnostic tools, and therapy responses published in the literature. In 2018, Al-Tabbaa and Habal 5 reported the case of a 25-year-old man who developed meningoencephalitis secondary to RP that was refractory to all high-dose immunosuppressive medications. Of the 19 prior cases of RP with meningoencephalitis reported to date, this was the first report to demonstrate a lack of response to immunosuppressive therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RP is a rare multisystem disorder affecting cartilaginous tissue and the CNS. The phenotype of RP in the CNS commonly manifests as meningoencephalitis and dementia [10][11][12][13][14][15][16]. Case 2 had abnormal mental behavior, memory loss, headache, and abnormal MRI, consistent with the features of RPrelated encephalitis.…”
Section: Discussionmentioning
confidence: 99%